2017
DOI: 10.1186/s13065-017-0255-7
|View full text |Cite
|
Sign up to set email alerts
|

A facile synthesis and anticancer activity of some novel thiazoles carrying 1,3,4-thiadiazole moiety

Abstract: BackgroundThiazoles and 1,3,4-thiadiazoles have been reported to possess various pharmacological activities.ResultsA novel series of thiazoles carrying 1,3,4-thiadiazole core were designed and prepared via the reaction of the 2-(4-methyl-2-phenylthiazole-5-carbonyl)-N-phenylhydrazinecarbo-thioamide with the appropriate hydrazonoyl chlorides. The structures of the newly synthesized compounds were confirmed based on elemental and spectral analysis as well as their alternative syntheses. The cytotoxic potency of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 54 publications
(26 citation statements)
references
References 41 publications
2
24
0
Order By: Relevance
“…In view of these precedents and together with our research concerns of developing new convenient approaches for the synthesis of different heterocyclic systems with auspicious pharmacological activities [20,21,22,23,24,25], we present in this report an efficient synthesis of some new series of novel thiazole derivatives using chitosan-grafted-poly(vinyl pyridine) as an eco-friendly biopolymeric basic catalyst. Additionally, we have assessed a variety of biological activities for the newly synthesized compounds that demonstrated their potential antitumor, antimicrobial and hepatoprotective effectiveness.…”
Section: Introductionmentioning
confidence: 99%
“…In view of these precedents and together with our research concerns of developing new convenient approaches for the synthesis of different heterocyclic systems with auspicious pharmacological activities [20,21,22,23,24,25], we present in this report an efficient synthesis of some new series of novel thiazole derivatives using chitosan-grafted-poly(vinyl pyridine) as an eco-friendly biopolymeric basic catalyst. Additionally, we have assessed a variety of biological activities for the newly synthesized compounds that demonstrated their potential antitumor, antimicrobial and hepatoprotective effectiveness.…”
Section: Introductionmentioning
confidence: 99%
“…Thiadiazoles have a wide range of pharmaceutical activities including anti‐inflammatory , antifungal , antibacterial , analgesic , antitubercular , and antileishmanicidal agents . Moreover, 1,3,4‐thiadiazoles are also important classes of azoles which have significant biological properties as antiviral and anticancer . Several studies have shown that two or three heterogeneous atoms such as nitrogen and sulfur are expected to have antimicrobial activities .…”
Section: Introductionmentioning
confidence: 99%
“…Pyrazolines have been found to possess diverse biological activities such as anticancer [ 2 , 3 , 4 ], antitumor [ 5 ], antioxidant [ 6 ], antimicrobial [ 7 , 8 ], antitubercular [ 9 ], antimalarial [ 10 ], anti-amoebic [ 11 ], DPPH radical scavenging, anti-diabetic [ 12 ], antiviral [ 13 ] and amine oxidase [ 14 ]. Also, thiazoles are known to have anticonvulsant [ 15 ], antimicrobial [ 16 ], anti-inflammatory [ 17 ], anticancer [ 18 , 19 , 20 ], antidiabetic [ 21 ], anti-HIV [ 22 ], anti-Alzheimer [ 23 ], antihypertensive [ 24 ], antifungal [ 25 ], and antioxidant [ 26 ] activities. In view of the above mentioned findings and as a part of our research interest towards developing new ways to synthesize a variety of heterocyclic systems with promising biological and pharmacological activities [ 27 , 28 , 29 , 30 ], we present in this research an efficient synthesis of a series of pyrazolines attached to thiazole moiety using N -thiocarbamoylpyrazoline [ 31 ] and the appropriate hydrazonoyl halides [ 32 , 33 , 34 ] or α-haloketones in the presence of DABCO under the solvent-drop grinding method [ 35 ].…”
Section: Introductionmentioning
confidence: 99%